Pay Differentials between Government and Private Sector Employees in Sweden - Siv Gustafsson (The Research Institute of Industrial Economics (IUI), 1977)
The human capital model predicts that in equilibrium and in the absence of discrimination units of human capital possessed by individuals are paid the same rentals. This would hold also when comparing private and government sectors. Only non-pecuniary rewards such as better job security of fringe benefits would lead to acceptance of lower money payment. In Sweden salary differentials standardized for human capital variables are found to be in favour of private sector employment. This result contrasts with recent findings for the USA where the reverse was found.
Keywords: J31; J45; 330; Wage; Private sector; Public sector